An Image Processing Online Laboratory within the iLab Shared Architecture - Niederstaetter, Michael; Klinger, Thomas; Garbi Zutin, Danilo (International Journal of Online and Biomedical Engineering (iJOE), 2010)
This paper focuses on a new way for students to deepen their knowledge in image processing and analysis with the help of an online laboratory. The existing solution provides a remotely controlled visual presenter which is used to project a document or book to various kinds of screens. The visual presenter can be controlled remotely and it provides the possibility to design, create and upload your own autofocus algorithm. Via the serial port and an image acquisition card the visual presenter can be controlled with the LabVIEW 8.6 software (National instruments, USA). Because of numerous advantages such as single login and reservation system for more online laboratories the whole experiment is realized within the iLab shared architecture.